EMPLOYEE VOICE BEHAVIOR AND ORGANIZATIONAL CLIMATE: EVIDENCE FROM MANUFACTURING COMPANIES IN NIGERIA - Ugo Chuks Okolie; Oyovwevotu V. Erakpotobo; Ndubuisi J. Memeh (Universitas Pendidikan Indonesia, 2023)
This study investigates the effect of employee voice behavior on organizational climate of manufacturing firms in Nigeria. It used a cross-sectional survey research design and Data were gathered as of February 21, 2023, from middle and lower level employees of manufacturing companies registered under the Manufacturing Association of Nigeria, Delta Edo Chapter. Ten businesses with a combined staff of 2,017 were chosen for the study's purposes. Using Taro Yamane's formula, a sample of 334 employees was created and only 287 responses were retrieved. After a multicollinearity test and correlation matrix revealed no collinearity issues, the hypothesis were tested with linear regression. Results of hypothesis tested showed that participation has positive significant relationship with organizational climate. Additionally, a positive, significant relationship between involvement and organizational climate was discovered. According to the study's findings, employee voice behavior that is measured in terms of participation and involvement enhances the organizational climate, which fosters coworker support, management recognition, creativity, and equity among all group members. The study advises manufacturing firms' top management to recognize the necessity of regularly involving middle and lower level employees in their decision-making processes, whether directly or through advisory participation, in order to continuously increase organizational effectiveness.